CGIAR Research Program on climate change, agriculture and food security factsheet - WorldFish (WorldFish, 2014)
Climate change is an unprecedented threat to the food security of hundreds of millions of people. Climate change affects agriculture and food security, and likewise, agriculture and natural resource management affect the climate system. These complex and dynamic relationships are also shaped by economic policies, political conflict and other factors such as the spread of infectious diseases. The relationships between all these factors and how they interact are not well understood, nor are the advantages and disadvantages of different responses to climate change. In order to develop practical solutions for agriculture in the face of climate change, knowledge about climate change, agriculture and food security needs to be integrated in meaningful and innovative ways. The CGIAR Research Program on Climate Change, Agriculture and Food Security seeks to promote food security through sustainable agriculture and by exploring new ways of helping vulnerable rural communities adjust to global changes in climate while conserving natural resources.